Solubility of non-aromatic hexafluorophosphate-based salts and ionic liquids in water determined by electrical conductivity - Neves, Catarina M. S. S.
The knowledge of the salts solubility in water is of major interest for process design and optimization and for environmental monitoring. The determination of the water solubility of non-aromatic salts or ionic liquids requires the use of specific and expensive analytical equipment. In this work the use of electrical conductivity for the quantification of the solubility of sparingly soluble salts in water is proposed. Novel data for the water solubility of 1-methyl-1-propylpyrrolidinium hexafluorophosphate, 1-methyl-1-propylpiperidinium hexafluorophosphate, tetrabutylammonium hexafluorophosphate, and tetrabutylphosphonium hexafluorophosphate, in the temperature range from 288.15 to 318.15 K, are reported. Using the gathered results, along with literature data, a correlation between the aqueous solubility of [PF6]-based salts with their molar volume is proposed. The COSMO-RS predictive model was also used to estimate the solid-liquid equilibrium of the investigated systems. Since all the compounds are solid at room temperature, they were further characterized by differential scanning calorimetry, and the temperatures of solid-solid and solid-liquid phase transitions, as well as the respective enthalpies of phase transition, are presented. (C) 2013 Elsevier B.V. All rights reserved.